Internal Control Systems and Financial Performance of NGOS: A Case of Association Of Volunteers In Service International (Avsi) Kabale Branch - Uganda. - Agwate, Doreen (Kabale University, 2023)
The study was conducted from AVSI Uganda Kabale branch to establish the relation between internal control systems and financial performance of NGOs. The independent variables in the study included control environment, compliance with rules and information communication technology whereas the dependent variable was financial performance. The study followed a descriptive design. Data was collected from 100 respondents. Since descriptive analysis entailed description of a single variable and its attributes, frequency tables were used to present the data. At the bi-variate level, a Pearson correlation matrix was conducted to ascertain the relationships between the predictor variables and the dependent variable. Research findings showed that control environment = 0.630, information communication technology =0.585 and compliance with rules =0.649. The researcher came to a conclusion that information communication technology, compliance with rules and regulations and control environment have a positive significant relationship on financial performance of AVSI Uganda. The study recommended that processes should be improved and strengthened to ensure that there is ongoing and independent reconciliation of all AVSI balances, both asset and liability and on- and off balance sheet items. Policies and procedures should also exist to ensure that decisions are made with appropriate approvals.